EPIDEMIOLOGICAL CHARACTERISTICS OF AIDS AND ORGANIZATION OF EPIDEMIOLOGICAL SURVEILLANCE (Journal of Universal Science Research, 2025)
According to the World Health Organization, approximately 88.4 million people worldwide have been infected with AIDS since the beginning of the epidemic, and 42.3 million of them have died. According to the United Nations, AIDS/HIV ranks as the 5th leading cause of death among diseases today. The number of people living with the disease exceeds 39.9 million globally. Women account for 44% of those infected with AIDS, while the remaining percentage are men. Worldwide, 86% of infected individuals are aware that they have contracted HIV, while the rest continue to live without knowing their status.